2017
DOI: 10.1007/s10897-017-0067-x
|View full text |Cite
|
Sign up to set email alerts
|

A Rapid Systematic Review of Outcomes Studies in Genetic Counseling

Abstract: As healthcare reimbursement is increasingly tied to value-of-service, it is critical for the genetic counselor (GC) profession to demonstrate the value added by GCs through outcomes research. We conducted a rapid systematic literature review to identify outcomes of genetic counseling. Web of Science (including PubMed) and CINAHL databases were systematically searched to identify articles meeting the following criteria: 1) measures were assessed before and after genetic counseling (pre-post design) or compariso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
97
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 99 publications
(106 citation statements)
references
References 38 publications
8
97
0
1
Order By: Relevance
“…Evidence from this review suggests that race and ethnicity may have little to no effect on outcomes of anxiety, depression, or distress following genetic counseling, which is similar to the overall White population. Results indicating unchanged anxiety or distress are in agreement with research of general or majority populations (Madlensky et al, ; Watson et al, ), and thus may not be a noteworthy differentiator. However, racial and ethnic differences in risk perception, expectations of genetic counselors, overall satisfaction, and test result communication were supported by single studies and replication is encouraged.…”
Section: Discussionsupporting
confidence: 86%
“…Evidence from this review suggests that race and ethnicity may have little to no effect on outcomes of anxiety, depression, or distress following genetic counseling, which is similar to the overall White population. Results indicating unchanged anxiety or distress are in agreement with research of general or majority populations (Madlensky et al, ; Watson et al, ), and thus may not be a noteworthy differentiator. However, racial and ethnic differences in risk perception, expectations of genetic counselors, overall satisfaction, and test result communication were supported by single studies and replication is encouraged.…”
Section: Discussionsupporting
confidence: 86%
“…The findings of this study describe patients’ perspectives on the process and outcomes of psychiatric GC and show that participants perceive counseling to be an “ empowering encounter ”. Until recently, the outcomes of GC services have focused on provider‐defined measures such as knowledge, risk perception, and decision‐making (Madlensky et al, ; McAllister, Dunn, & Todd, ). But as our understanding of the benefits of GC has evolved, our attention has turned to patient‐reported outcomes (Deshpande, Rajan, Sudeepthi, & Abdul, ), such as empowerment (McAllister & Dearing, ; McAllister et al, ) and adaptation to health threatening information (Biesecker et al, ), both of which have been identified as important outcomes of the GC process.…”
Section: Discussionmentioning
confidence: 99%
“…Genetic counseling provides an opportunity for breast cancer survivors to learn more about their risks for new primary cancers, and improve their outcomes, including reducing anxiety and cancer related distress [13]. In this study, we explored factors related to the Health Belief Model that may impact breast cancer survivors’ readiness to engage in genetic counseling.…”
Section: Discussionmentioning
confidence: 99%
“…Genetic counseling provides education and counseling about hereditary breast and ovarian cancer and the process, risk and benefits of genetic testing [12]. Studies found breast cancer patients who attend genetic counseling have increased knowledge about cancer genetics, improved risk perception accuracy, and reduced anxiety and cancer related distress [13, 14]. Although the patient is responsible for the decision to engage in a health care consultation, our team and others found patients chose not to attend genetic counseling based on incomplete knowledge (e.g., misperceptions about genetic counseling/testing processes), inaccurate health beliefs (e.g., perceived susceptibility, benefits or barriers), and psychosocial factors (e.g., feeling overwhelmed with the cancer diagnosis) [8, 15–17].…”
Section: Introductionmentioning
confidence: 99%